Біохімічна характеристика сировини Camelina sativa (L.) Crantz - Vergun, O.M.; Rakhmetov, D.B.; Shymanska, O.V.; Fishchenko, V.V.; Druz, N.G.; Rakhmetova, S.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
Objective – to study the content of nutrients in the plants of different varieties and cultivars of Camelina sativa (L.) Crantz in the flowering stage. Material and methods. Investigations were carried out with cultivars and varieties of C. sativa own selection. We used to research the laboratory methods. Results. It was marked the accumulation of dry matter from 18.13 % (сv. Peremoha) to 23.38 % (сv. Kolondaik), ascorbic acid – from 207.23 mg% (сv. Kolondaik) to 410.23 mg% (сv. Pivnichna krasunya), carotene – from 0.43 mg% (сv. Yevro-12) to 2.23 mg% (сv. Peremoha), ash – from 5.08 % (сv. Kolondaik) to 8.75 % (f. ЕОRZHI AF-1), calcium – from 1.008 % (сv. Yevro-12) to 2.633 % (сv. Kolondaik), phosphorus – from 0.086 % (сv. Mirazh) to 0.157 % (f. ЕОRZHIAF-1), the total content of sugars – from 4.76 % (f. ЕОRZHIAFCH) to 8.12 % (сv. Peremoha). Power plant value of investigated plants was from 3925.71 to 4097.00 kkal/kg that depends on cultivar and variety. The content of pigments and their ration are determined. The ration of chlorophylls was from 2.51 (сv. Yevro-12) to 2.82 (сv. Pivnichna krasunya), chlorophylls to carotenoids – from 1.99 (сv. Pivnichna krasunya) to 3.22 (сv. Mirazh). Research of antioxidant activity by DPPH-method (reaction with 2.2-diphenyl-1-picrylhydrazyl radical) shown that the methanol extracts from above-ground part of plants inhibited the activity of radical on 25.67–55.88 % and water extracts – on 47.18–84.60 % that depends from cultivar or variety. Conclusions. The raw plant material of C. sativa is potent source of the vitamins, macroelements, ash and total content of sugars. These plants can compete with the other energetic cultures by energetic value.